The biological effect of the nitroimidazole derivative of a polypyridyl ruthenium complex on cancer and endothelial cells1. Issue 3 (11th March 2015) - Mazuryk, Olga; Suzenet, Franck; Kieda, Claudine; Brindell, Małgorzata
<x xml:space="preserve">Abstract</x> The studied Ru polypyridyl complexes are ca. ten times more cytotoxic against breast cancer (4T1) and human lung adenocarcinoma epithelial cells (A549) than cisplatin and have a distinct impact on cell adhesion, migration and endothelial cell vasculature.